Mupu Jeruk Attractions as a Sustainable Tourism Alternative - Imaddudin Imaddudin; Francisca Titing Koerniawaty; Firman Sinaga (Enrichment : Journal of Management, 2022)
Tourism acts as a leading sector that will help the recovery of other sectors in the tourism supply chain. The potential of agro-tourism becomes a sustainable tourism opportunity by playing an integrated 4A role. This study aims to analyze the potential of sustainable 4A tourism in special interest tourism. This study uses a qualitative descriptive method through data collection by means of observation, and in-depth interviews supported by a SWOT analysis from the side of sustainable tourism 4A (Attractions, Accessibility, Ancilliary, and Amenity). The results showed that Mupu Jeruk provides a unique experience by picking fruit and getting education and entertainment that is integrated with the concept of tourism and has tourism potential to be developed into a tourist destination of particular interest as an alternative to fruit picking and edutainment tourism supported by 4A which can attract stakeholders. as a promised development prospect